Exploring the Role of Islamic Value Proposition, Digital Customer Experience, and Trust on Customer Satisfaction in Islamic Banking: Evidence from Indonesia's Emerging Market - Admiral Danarhuda; Nihayatu Aslamatis Solekah (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Customer satisfaction remains a crucial determinant of competitiveness in the Islamic banking sector, particularly within Indonesia's rapidly expanding emerging market. Despite continuous growth, many Islamic banks still face challenges in maintaining consistent service quality and aligning customer experience with Sharia-based values. This study examines the impact of Islamic value proposition, digital customer experience, and trust on shaping customer satisfaction at Bank Syariah Indonesia (BSI). Positioned within the broader discourse on ethical and Sharia-compliant marketing, this research employs a quantitative descriptive design, using purposive sampling to survey 150 BSI customers through structured questionnaires. Data were analysed using multiple linear regression with SPSS 23 to assess both individual and joint effects of the variables. The findings reveal that the Islamic value proposition and digital customer experience have a significant influence on customer satisfaction, while trust shows no direct effect. Collectively, these variables exert a positive and significant impact, highlighting the importance of integrating Islamic ethical values and digital innovation to strengthen customer loyalty in Islamic banking.